Delineamentos jurídico-normativos da educação inclusiva problematização a partir das noções foucaultianas de governamentalidade e biopolítica - Martins, Thiago Vaceli (Editora Oficina Universitária, 2023)
The book addresses the theme of inclusion of people with disabilities in the educational field, correlating the activism of the legislative and judiciary powers and the perspective of complying with the laws that govern inclusion policies in Brazil, since the 1988 Constitution. they arise, above all, from the struggles for civil rights demanded individually or by communities of people with disabilities. A relevant theme is presented for the debates on important aspects for our Education, for our teaching, for the Teaching of History and, especially, for the analysis of what is prescribed as inclusive and what really materializes as such in our schools. The State and the constituted public authorities must be connected in terms of the rationale for regulating differences, tuning inclusion policies that strengthen and respect the condition of people with disabilities, guaranteeing their presence as an element or subject to rights, in the sphere of individual rights and also in the public sphere. The work emphasizes the power of educational policies as an element of transformation, especially when they express the power of the capacity of people with disabilities, respecting their difference, which is unique, with activism being decisive for the construction of inclusive education networks and an important means of ensure educational public policies that contemplate - and respect, ethically, these differences. The book may be of interest to those who are interested in looking into the "activism" of the legislature and the judiciary regarding inclusion, particularly in the field of Law and Education.